2018
DOI: 10.1016/j.ihj.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning for prevention of contrast induced nephropathy—Insights from an Indian study

Abstract: ObjectivesTo study if four cycles of remote ischemic preconditioning (RIPC) could offer protection against contrast induced nephropathy (CIN) and post procedural renal dysfunction in high risk patients undergoing percutaneous coronary intervention (PCI).MethodsThis was a prospective single blind randomized sham controlled trial where patients undergoing coronary angioplasty with stage III chronic kidney disease were randomized into sham preconditioning and remote ischemic preconditioning. The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, Hu et al [51] included 10 RCTs with 1,167 patients, and Bei et al [50] included 7 RCTs with 957 patients, whereas the present study included 16 RCTs with 2,048 patients. Inconsistent with the results of these 2 meta-analyses, 3 recent trials reported that RIPC did not significantly reduce CIN [29, 30, 35]. Here, we included 6 updated additional RCTs to assess the effect of RIPC for CIN in a more comprehensive manner.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, Hu et al [51] included 10 RCTs with 1,167 patients, and Bei et al [50] included 7 RCTs with 957 patients, whereas the present study included 16 RCTs with 2,048 patients. Inconsistent with the results of these 2 meta-analyses, 3 recent trials reported that RIPC did not significantly reduce CIN [29, 30, 35]. Here, we included 6 updated additional RCTs to assess the effect of RIPC for CIN in a more comprehensive manner.…”
Section: Discussionmentioning
confidence: 87%
“…In the study by Er et al [18], the level of serum creatinine was significantly higher after 48 h in control patients compared to patients with RIPC. Valappil et al [29] showed that there was a statistically significant reduction in the serum creatinine at 24 h, 48 h, 2 weeks, and 6 weeks in the RIPC group compared to the sham group. However, Ghaemian et al [22] found that there was no statistically significant difference between the RIPC and control groups in serum creatinine levels 48–72 h after the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with a moderate-to-high risk of CIN, who underwent IA CM injection for CA or percutaneous coronary angioplasty, the effects of RIPC are controversial, with several controlled studies demonstrating that RIPC reduces the incidence of CIN ( 14 15 16 17 24 ), while others reported no difference in the incidence of CIN ( 19 21 22 ). However, several meta-analyses have concluded that RIPC is effective in reducing the risk of CIN ( 26 27 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The principal evaluation criterion was the incidence of CIN, defined as an increase in the serum creatinine levels higher than or equal to the value of 0.5 mg/dL or a relative increase of 25%, 48 hours after the CM injection, as stated in similar previous publications ( 14 15 21 22 23 24 ).…”
Section: Methodsmentioning
confidence: 99%